2014
DOI: 10.2147/cia.s57714
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated alterations in cholesterol homeostasis: evidence from a cross-sectional study in a Northern Italy population

Abstract: BackgroundThe modifications of cholesterol metabolism associated with aging are ill-defined. The objective of this study was to define age-associated alterations of the different metabolic pathways controlling cholesterol homeostasis by analyzing circulating sterols.MethodsWe analyzed serum samples collected from 201 adult (75 male, 126 female) subjects within the epidemiological MICOL study (Multicentrica Italiana Colelitiasi). The age range was 38–79 years; 103 had evidence of gallstones. The concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 42 publications
1
27
0
2
Order By: Relevance
“…It is important to mention that aging’s effect on cholesterol homeostasis is poorly defined. A number of epidemiological studies suggest that serum cholesterol levels tend to increase in adults, but subsequently decrease in the very elderly [43]. Similarly, it has been found that obese young and older patients showed significantly higher cholesterol and TG plasma levels compared with their control age matched groups [44].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that aging’s effect on cholesterol homeostasis is poorly defined. A number of epidemiological studies suggest that serum cholesterol levels tend to increase in adults, but subsequently decrease in the very elderly [43]. Similarly, it has been found that obese young and older patients showed significantly higher cholesterol and TG plasma levels compared with their control age matched groups [44].…”
Section: Discussionmentioning
confidence: 99%
“…Data in humans largely derive from the analysis of plasma levels of hydroxylated sterols, which are currently regarded as reliable markers of cholesterol absorption efficiency, such as sitosterol and campesterol. The ratios of sitosterol to cholesterol and campesterol to cholesterol were found to be either unaffected or reduced with aging; therefore, it seems unlikely that changes in intestinal absorption might underlie the observed increase in plasma cholesterol.…”
Section: Age‐associated Changes In Cholesterol Homeostasismentioning
confidence: 92%
“…In humans, circulating levels of biosynthetic precursors of cholesterol, in particular the lathosterol to cholesterol ratio, were utilized as markers of cholesterol synthesis. The evidence in the literature is conflicting, bringing either evidence of a reduction of synthesis markers or no change with aging. Once again, the changes in this metabolic process tend to be less pronounced in the oldest strata.…”
Section: Age‐associated Changes In Cholesterol Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, production of free oxygen radicals is generated by the cytochrome P450 4A and 2E1 isoenzymes-lypoxygenases [12] . Age-related data even though still undefined might reveal some connection of alterations in cholesterol synthesis in patients with NAFLD [13] . Finally this lipid peroxidation leads to the release of malondial-dehyde and 4-hydroxynonenal, which causes cell death and protein cross-linkage, resulting in the formation of Mallory's hyaline in the hepatocyte [14] .…”
Section: Pathogenesismentioning
confidence: 99%